PENGARUH BUDAYA KERJA, KEMAMPUAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI MENJELANG MASA PURNABAKTI PADA LINGKUP KANWIL DITJEN PERBENDAHARAAN PROVINSI D. I. YOGYAKARTA - Sugeng Widodo; Abdul Choliq Hidayat; Aftoni Sutanto (Value : Jurnal Manajemen dan Akuntansi, 2021)
Employee performance is a discussion that has never been bored to be examined from various points of view. This time the author tries to present employee performance when faced with conditions at the end of the productive age (before retirement). This research provides an understanding of how employees actually ahead of their retirement, how to work culture and the ability whether they still have maximum enthusiasm. More specifically the purpose of this study to test Employee performance is a discussion that has never been bored to be examined from various points of view. This time the author tries to present employee performance when faced with conditions at the end of the productive age (before retirement). This research provides an understanding of how employees actually ahead of their retirement, how to work culture and the ability whether they still have maximum enthusiasm. More specifically the purpose of this study to test: (1) The influence of work culture on employee performance before retirement at the Regional Office of the Directorate General of Treasury, D. I. Yogyakarta Province; (2) The effect of work ability on employee performance prior to retirement at the Regional Office of the Directorate General of Treasury, D. I. Yogyakarta Province; (3) The influence of organizational commitment on employee performance prior to retirement at the Regional Office of the Directorate General of Treasury, D. I. Yogyakarta Province; and (4) The influence of work culture, work ability, and organizational commitment to employee performance prior to retirement at the Regional Office of the Directorate General of Treasury, D. I. Yogyakarta Province.This type of research used in this research was quantitative. The population in this study were all employees of the Regional Office of the Directorate General of Treasury of the Province D. I. Yogyakarta who will enter their retirement period within the next 5 (five) years starting from 2020 to 2025 totaling 60 employees. The sampling technique in this study was a census or total sample, namely the entire sample of 60 employees. The data collection technique used a questionnaire. The data analysis technique used multiple linear regression analysis. Based on the results of the research that has been done, the following conclusions are obtained: (1) Work culture has a positive and significant effect on employee performance before retirement in the Regional Office of the Directorate General of Provincial Treasury In Yogyakarta. (2) Job ability has a positive and significant effect on employee performance prior to retirement at the Regional Office of the Directorate General of Treasury, Province D. I. Yogyakarta. (3) Organizational commitment has a positive and significant effect on employee performance before retirement at the Regional Office of the Directorate General of Treasury, Province D. I. Yogyakarta. (4) Work culture, work ability, and organizational commitment have a positive and significant effect together on employee performance prior to retirement at the Regional Office of the Directorate General of Treasury, D. I. Yogyakarta Province. Keywords: work culture, work ability, organizational commitment, employee performance.